math
posted by Anonymous on .
(4x)^2/3=(30x+4)^1/3
please explain=)

(4x)^(2/3) = (30x+4)^(1/3)
To do this, note that it's much easier to work with whole number exponents. This we raise both side terms by 3, so that the denominator 3 will be cancelled:
(4x)^(2/3 * 3) = (30x+4)^(1/3 * 3)
(4x)^2 = (30x+4)^1
16x^2 = 30x + 4
Solving for x,
8x^2  15x  2 = 0
(8x + 1)(x  2) = 0
x = 2
x = 1/8
Then we check by substituting these x values to the original equation:
i. x = 2
(4x)^(2/3) = (30x+4)^(1/3)
(4*2)^(2/3) = (30*2+4)^(1/3)
(8)^(2/3) = 64^(1/3)
2^2 = 4
4 = 4
Thus x is indeed equal to 2.
ii. x = 1/8
(4x)^(2/3) = (30x+4)^(1/3)
(4*(1/8))^(2/3) = (30*(1/8)+4)^(1/3)
(1/2)^(2/3) = (15/4 + 16/4)^(1/3)
(1/4)^(1/3) = (1/4)^(1/3)
Thus x is also equal to 1/8.
Hope this helps~ :3 
i didn't get how 16x^2 turned into 8x^2
16x^2 = 30x + 4
Solving for x,
8x^2  15x  2 = 0